Symbolic Values in Mandala Painting by I Dewa Nyoman Batuan - I Made Ruta; I Ketut Suda; I Gusti Bagus Wirawan (International Journal of Interreligious and Intercultural Studies, 2025)
Bali is well known for its art and culture, both nationally and internationally. Therefore, it is not surprising that in Bali, art and culture have developed very rapidly, including painting. In the 1930s, a new Balinese painting emerged whose subject matter was people in everyday life. For example, ritual activities in temples, rice harvesting scenes, traditional festival processions, crowded market scenes, and animal life became the central themes of Balinese painters' artworks. However, the issue of art, especially painting in Bali, is not widely studied academically by artists, especially by naturalist artists. In fact, the main painting by I Dewa Nyoman Batuan contains many symbolic values, both religious symbols and cultural symbols, especially Hindu religion and culture. The problem is why paintings by I Dewa Nyoman Batuan are said to contain high symbolic value? Then how is the visualization of symbolic values in the works of I Dewa Nyoman Batuan, and what are the implications for social, cultural, religious life, and for the life of art itself. This research uses a qualitative approach with qualitative-interpretative analysis techniques. Data collection techniques were carried out by observation, in-depth interviews, and document studies. The results obtained, namely there are several factors that cause mandala painting art by I Dewa Nyoman Batuan to be said to contain high simbolic value, such as philosophical factors, ideological factors, theological factors, and the use of symbols in religious and cultural life. Then the forms of visualization of symbolic values in the painting by I Dewa Nyoman Batuan are visualization in the form of the puppet world, flora and fauna, and visualization in the form of a round mandala. The content of these symbolic values has implications for social life, culture, religion, and the life of art itself. Interesting findings obtained in this study are factually this study found that the mandala painting art by I Dewa Nyoman Batuan has advantages, namely the content of symbolic values, in its presentation there is an integration pattern between internal factors called taksu with environmental factors. This can be seen from the genes passed down by his grandfather I Dewa Nyoman Batuan, who was also a painter, and then supported by the environment where Pengosekan Village is a center for painting crafts that shape the personality of I Dewa Nyoman Batuan as a painter with character. Meanwhile, the theoretical findings affirm aesthetic theory, semiotic theory, and value theory in the sense that the three theories also seem to apply in this research location